2013
DOI: 10.1080/15389588.2012.689451
|View full text |Cite
|
Sign up to set email alerts
|

Can Patients Receiving Opioid Maintenance Therapy Safely Drive? A Systematic Review of Epidemiological and Experimental Studies on Driving Ability With a Focus on Concomitant Methadone or Buprenorphine Administration

Abstract: Both methadone and buprenorphine were confirmed as having impairing potentials in opioid-naïve subjects. At least some opioid maintenance therapy patients are observed having only slight impairments of relevance to driving. Knowing this when approaching the question of ability to drive, an individual evaluation of the driving performance, pertaining to the opioid maintained patient, may be the most useful and conclusive procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 66 publications
(93 reference statements)
1
34
0
1
Order By: Relevance
“…Two randomized controlled trials found no significant effect of opioids on driving performance [10,11], whereas other studies suggest that opioids can lead to impairment in driving abilities [13,14]. Our data did not show any significant difference in the rate of motor vehicle collision between patients taking narcotics and those not taking narcotics.…”
Section: Discussionmentioning
confidence: 52%
“…Two randomized controlled trials found no significant effect of opioids on driving performance [10,11], whereas other studies suggest that opioids can lead to impairment in driving abilities [13,14]. Our data did not show any significant difference in the rate of motor vehicle collision between patients taking narcotics and those not taking narcotics.…”
Section: Discussionmentioning
confidence: 52%
“…Some studies have suggested that opioids improve concentration, executive function [80], psychomotor function [81] and scores on neurocognitive testing [82]. Yet other studies find that chronic opioid exposure is associated with impaired cognitive processing and psychomotor functions [83][84][85]. Opioid naïve subjects demonstrate impaired cognitive and psychomotor function after administration of a single dose of methadone or buprenorphine [83].…”
Section: Opioids and Functional Outcomesmentioning
confidence: 97%
“…Yet other studies find that chronic opioid exposure is associated with impaired cognitive processing and psychomotor functions [83][84][85]. Opioid naïve subjects demonstrate impaired cognitive and psychomotor function after administration of a single dose of methadone or buprenorphine [83]. Chronic opioid exposure is associated with deficits across a range of neuropsychological domains with robust impairment in verbal working memory and cognitive impulsivity (risk taking) alongwith cognitive flexibility (verbal fluency) [85].…”
Section: Opioids and Functional Outcomesmentioning
confidence: 98%
“…An important aspect of this debate is the association between drugs of abuse and traffic safety. Alcohol, opioids, and benzodiazepines have been irrefutably linked with motor vehicle collisions and mortality [3][4][5]. The consumption of cannabis has also been correlated with an increased risk of traffic accidents based on epidemiological studies [6].…”
Section: Introductionmentioning
confidence: 99%